Еfficiacy and safety of radium-223 in the treatment of metastatic castration-resistant prostate cancer - I. G. Rusakov (Медицинский совет, 2020)
Bone metastases often develop in patients with prostate cancer (PC) as a natural stage in the course of the disease. The skeletal system is the most typical and sometimes even the only site of metastatic prostate cancer. The involvement of bones is a cause of reduced life expectancy and a strong prognostic factor for adverse events, such as bone complications (including the pain requiring surgery or palliative radiation therapy, pathologic fractures and spinal cord compression), resulting in a significant decrease in the quality of life.The model of therapeutic decision-making in metastatic castration-resistant PC (mCRPC) is still an unsolved problem. Several therapeutic options have been developed recently, that has significantly improved the survival of patients with mCRPC. The presence of multiple active agents provides oncologists with an unprecedented opportunity to tailor their choices to the clinical characteristics of each patient and to each line of treatment, but at the same time it creates the challenge of determining the optimal therapeutic sequence for the individual patient.In Russia, radium-223 is approved for patients having bone metastases and no visceral metastases. It can be assigned to patients with lymph node metastases and patients with bulky bone metastases if other drugs are contraindicated to them. However, the use of radium-223 is most preferable if a patient has bone metastases and good bone marrow reserve.Due to the evolution of treatment strategies, the complexity of the process of assessing the dynamics of treatment and the variability of the clinical aspects of the disease, a multidisciplinary approach becomes of great importance today.